Global Contrasts Between Oceanic Cycling of Cadmium and Phosphate. Issue 6 (8th June 2021) - Roshan, Saeed; DeVries, Tim
Abstract: Cadmium (Cd) is a trace metal whose distribution in the ocean bears a remarkable resemblance to the nutrient phosphate (PO4 3− ). This resemblance has led to the use of Cd as a proxy for ocean nutrient cycling in paleoceanographic applications, but the processes governing the cycling of Cd in the modern ocean remain unclear. In this study, we use previously published Cd observations and an Artificial Neural Network to produce a dissolved Cd climatology that reproduces the observed subtle deviations between the Cd and PO 4 3 − distributions. We use the Cd and PO 4 3 − climatologies, along with an ocean circulation inverse model, to diagnose the biogeochemical sources and sinks of dissolved Cd and PO 4 3 − . Our calculations reveal that dissolved Cd, like PO 4 3 −, is removed in the surface ocean and has a source in the subsurface, consistent with the simultaneous incorporation of Cd and PO 4 3 − into sinking organic particles. However, there are also contrasts between the cycling of dissolved Cd and PO 4 3 − . In particular, the Cd:PO 4 3 − surface export ratio varies 8‐fold across latitudes, reaching highest values in the iron‐limited sub‐Antarctic Southern Ocean. This depletes Cd relative to PO 4 3 − in the low‐latitude thermocline while adding excess Cd to deep waters by the regeneration of Cd‐enriched particles. Also, Cd tends to regenerate slightly deeper than PO 4 3 − in the subsurface ocean, and the Cd:PO 4 3 − regeneration ratio reaches a maximum at 700–1, 500 m. These contrasts are responsible for a slight concavity in the Cd ‐ PO 4 3 − relationship and should be considered when interpreting paleoceanographic Cd records. Key Points: We derive a climatology of dissolved Cadmium (Cd), and use it to calculate the biogeochemical sources and sinks of Cd in the ocean Preferential Cd uptake in the Southern Ocean depletes the low‐latitude thermocline of Cd and pumps Cd into deep water masses Cd tends to regenerate slightly deeper than PO 4 3 −, except in low‐oxygen regions where the opposite is true